Analysis on law issues toward abandoned building housing and project in peninsular, Malaysia - Nor Zuraiha, Mohd Zaki (2019)
The abandoned building projects became seriousness problem in Malaysia because this problem became increase over the year. Therefore, lack of awareness of the distressing problem of abandoned unless our government to enlighten the public either involved in the project was abandoned or not. Moreover, the government also already has their own legal about housing sector but that problem still happens. The purpose of this study is to analysis on law issues toward abandoned building project and the impact that caused by abandoned building project in Peninsular, Malaysia. The literature review in this study is to identified the law issues toward abandoned building project. The method used in this study to collect the data is distributing the questionnaire survey and interviews with five (5) person that involve in construction industry. A total of 53 respondents was collected are representing developers, contractors, consultants, government and other that are related in construction industry. From the respondent’s point of view, the causes toward abandoned building due to Act is based on Act by government is Section 3 in Housing Development (Control and Licensing) Regulation 1989 and clause 69 in P.W.D Form 203A (Rev. 1/2010). The abandoned building project can give impact to the country because of Malaysia have a lack of legal action to abandoned building project. The finding could help the practitioners in construction industry to gain better understanding about the problems time of projects during construction stage.